Structure and Melodic Sabean Mandaean (Al-Academy, 2018)
The Mandaean religion of ancient and important religions in Iraq and Iran has its own rituals which are characterized by the use of singing and toning of speech. It began with the creation of human beings through a group of prophets. Peace be upon them. Researcher research problem, and explained the importance of research and objectives and limits and identify terminology. The second topic is the theoretical framework to include the history of the Sabean Mandaean, secondly their religious rites, sources, major books and secondary books for the Latin tribes of Mandaean. Finally, the researcher tackled the sources of their sacred books and previous studies. The third topic represented the procedures. The researcher dealt with the musical analysis and analysis system he prepared, The fourth topic is the analysis of the selected sample. The fifth section represents the results and the conclusions are based on the objectives required in this research. Then recommendations and proposals, followed by a list of resource margins, and finally a summary of the research and title in English